PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 018 SINTONG KECAMATAN TANAH PUTIH - Irma Susanti; Lazim N Lazim N; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Problems in research this is its low of result study class student IPA V SDN 018 Sintong with average class 62,27. from 30 student who finish 10 people whereas that don't finish 20 people. Completing Criteria value Maksimun (KKM)IPA is 65. this research is research Action of Class (PTK). this Research is done in two cycles that is four times material meeting and two times repeating of daily. data collection Instrument to research this is teacher's observation sheet and student also result test study. From show research data that studying process and studying result to undergo leveling. After to be applied Quantum Teaching model, research result show that activity of teacher to cycle I with average 59,37% enough categoryy, to meeting two cycles I 62,50% good categoryy.next to cycle meeting II first 78,12% good categoryy and to meeting two cycles II 90,62% categoryy very good. Activity of student to cycle I 56,25% enough categoryy, II's meeting I's cycle 68,75% good categoryy. next to cycle meeting II first be obtained persentase 81,25% categoryy very good whereas to two cycles meeting II be obtained persentase 96,62% categoryy very good. research result Data to undergo leveling, to base skor who finish 10 people (33,33%). to cycle I level until student who finish 18 people (60%) and to cycle II undergo leveling of completing, student who finish 28 people (93,30%) research data to be based can to be concluded that model implement Quantum Teaching can to level it result study the V SD class Country 018 Sintong.Key Word : Quantum Teaching Model, Result study IPA